2006
DOI: 10.1080/09540260600658270
|View full text |Cite
|
Sign up to set email alerts
|

The tsunami and its aftermath in Sri Lanka: Explorations of a Buddhist perspective

Abstract: This paper discusses the tsunami disaster in Sri Lanka with special reference to Buddhism, which is the majority religion in the island. The role of religious beliefs and of religion in general in strengthening coping skills is well known. Buddhism, with its specific views on the human condition and its use of psychological strategies, is almost unique among world religions. The Buddhist responses to the tsunami have been discussed widely, if largely informally, in Sri Lanka, and many concepts and practices ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 10 publications
1
39
0
Order By: Relevance
“…In the Palestinian refugee camps a significant relationship between household density and poorer health was found, but neither headache nor stomach ache were investigated [12,13]. The tendency for this population to somatise their psychological distress combined with the high household density could suggest that the association between objective crowding and reported physical symptoms in this study operated via the influence of subjective crowding on mental distress found by Ruback and Pandey and Fuller, Edwards et al [10,11,31,32]. …”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…In the Palestinian refugee camps a significant relationship between household density and poorer health was found, but neither headache nor stomach ache were investigated [12,13]. The tendency for this population to somatise their psychological distress combined with the high household density could suggest that the association between objective crowding and reported physical symptoms in this study operated via the influence of subjective crowding on mental distress found by Ruback and Pandey and Fuller, Edwards et al [10,11,31,32]. …”
Section: Discussionmentioning
confidence: 76%
“…Low socio-economic status and slow socio-economic recovery following a natural disaster [28,29], as well as the transitional camps themselves [30], have all been shown to be risk factors for poor psychological health outcomes. Carballo, Heal & Hernandez, De Silva, and Fernando have commented that Sri Lankans often present with somatisation rather than classic western symptoms of psychological distress [31-33]. Thus, it is possible that psychological distress associated with living in a transitional camp could explain a proportion of the high prevalence of reported pain symptoms of the IDP living there.…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive behaviour therapy (CBT) has been found to be effective in the management of patients with tsunami-related PTSD (Jarusuraisin & Kesornsukon, 2005, Piyasil et al, 2008 but this material should be adapted for local people and culture. In countries where Buddhism is widely practised, such as Sri Lanka and Thailand, the resilience shown by people in the aftermath of the tsunami has been recognized (de Silva, 2006;van Griensven et al, 2006) and their attitudes and beliefs of 'kamma' (or 'karma' in Sanskrit) is one explanation, but many questions still need further research to find the answers. The management of dead bodies was found to be a component of psychosocial interventions after the tsunami in Sri Lanka (Sumathipala, Siribaddana, & Perera, 2006).…”
Section: Psychosocial Interventions In Asiamentioning
confidence: 97%
“…In particular, research on the role of Buddhism in disaster recovery has been mixed, suggesting that the Buddhist value of acceptance may lead to indifferent or negative attitudes towards preparedness and mitigation (Levy, Slade, and Ranasinghe, 2009); or instead, cultivate directed action (De Silva, 2006), and therefore facilitate risk reduction. In particular, research on the role of Buddhism in disaster recovery has been mixed, suggesting that the Buddhist value of acceptance may lead to indifferent or negative attitudes towards preparedness and mitigation (Levy, Slade, and Ranasinghe, 2009); or instead, cultivate directed action (De Silva, 2006), and therefore facilitate risk reduction.…”
Section: Religious Attributionmentioning
confidence: 99%